Caracterização da piscicultura na microrregião da baixada Cuiabana, Mato Grosso, Brasil - de Barros, Adriana Fernandes; Martins, Maria Inez Espagnoli Geraldo [UNESP]; de Souza, Osvaldo Martins (My University, 2011)
The objective of this study was to characterize the fish farms located in the lowland micro region in Cuiabá, MT, through interviews with 26 selected farmers which represent the universe of fish farms that are active. Qualitative data were subjected to statistical Chi-square test to diagnose the existence of correlation between them with 95%confidence. These results support the conclusion that the species that compose the group of round fish are present in 100% of fish farms, accounting 88.2% of production. The difference is that production exclusively in nurseries and the largest area of shallow water, with production in higher scale than elsewhere in the country, with prospects of growth in area and productivity. Some actions should be implemented: legislation objectively and with sufficient qualified personnel to inspect the enterprises, applied research in food management and feed production with better price and quality, technical and administrative management, use of juveniles with proven genetics and monitoring of water quality. Fish farming is the main source of income funding for 67.5%of farmers interviewed. The size of the fish farms did not affect the variables related to implementation, conduct and management of the activity. The demand and price of feed are the variables that most directs the decision making of farmers. The main marketing channel used by medium and large farmers is exclusively, the slaughterhouses. The main part of fish is sold processed.
Characterization of fish farming in the Microregion lowland in Cuiabá, Mato Grosso, Brazil
Keywords: Fish farming; Round fish; Socio economic analysis